2019
DOI: 10.1111/tpj.14310
|View full text |Cite
|
Sign up to set email alerts
|

TsHD1 and TsNAC1 cooperatively play roles in plant growth and abiotic stress resistance of Thellungiella halophile

Abstract: Summary T. HALOPHILA HOMEOBOX PROTEIN 1(TsHD1) cloned from the halophyte Thellungiella halophila is a homeodomain (HD) transcription factor gene and functions as a collaborator of TsNAC1. TsHD1 can form heterodimers with TsNAC1 via the interaction between its zinc finger (ZF) domain and the A subdomain of TsNAC1. The overexpression of TsHD1 improved the heat stress resistance of T. halophila and retarded its vegetative growth slightly. The co‐overexpression of TsHD1 and TsNAC1 highly improved heat and drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The NAC recognition sequence CGT(G/A) and core DNA‐binding sequence CACG have been identified in the promoters of NAC‐targeted genes (Li et al ., 2019; Liu et al ., 2019; Xiang et al ., 2021). The putative ZmNAC49 binding elements were searched in the ZmSODs promoters and screened using luciferase assays.…”
Section: Resultsmentioning
confidence: 99%
“…The NAC recognition sequence CGT(G/A) and core DNA‐binding sequence CACG have been identified in the promoters of NAC‐targeted genes (Li et al ., 2019; Liu et al ., 2019; Xiang et al ., 2021). The putative ZmNAC49 binding elements were searched in the ZmSODs promoters and screened using luciferase assays.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the dimerization between the subdomain of NAC and other TFs plays an important role in the heat stress response. For example, TsHD1 cloned from the halophyte Thellungiella halophila, is a homeodomain (HD) TF gene that can improve heat tolerance by forming heterodimers through the interaction between the TsHD1 zinc finger domain and the A subdomain of TsNAC1 (Liu et al, 2019). Heat shock TFs (HSFs) and heat shock proteins (HSPs), which act as molecular chaperones for HSFs, are key TFs that respond to heat stress, NACs are likely to function as upstream regulators of HSFs (Figure 3a).…”
Section: Low-/high-temperature Stressmentioning
confidence: 99%
“…NAC TFs play important regulatory roles in various aspects of plant growth, development, and adaptation to the environment, including in shoot apical meristem formation [5], cell division and expansion [6,7] nutrient remobilization [8], flower formation [9], lateral root development [10,11], leaf senescence [12][13][14][15][16], secondary cell wall biosynthesis [3,[17][18][19][20], fiber development [19,21,22], fruit ripening [23,24], seed development [25], response to pathogen infection [26][27][28][29][30], and abiotic stress tolerance [31][32][33]. Many studies have confirmed that many NAC genes play crucial roles in the regulation of plant tolerance to drought.…”
Section: Introductionmentioning
confidence: 99%